The Genetic Relationships of Grevillea Hybrids Determined by RAPD Marker - MADE PHARMAWATI; IAN JAMES MACFARLANE (Bogor Agricultural University, Indonesia, 2013)
Grevillea (Proteaceae) is native to Australia and is known as garden plant. The flowers have high diversity colors, which range over orange, yellow, pink, red and green. It is a large genus, consisted of 357 species. This genus is economically important and there are hundreds of Grevillea hybrids with beautiful color and shape of flower. Information of the genetic relationships of Grevillea hybrids is not available. Ten Grevillea hybrids were used in this study to evaluate the genetic relationships between hybrids and with their parents. PCR-RAPD technique was employed in this study with seven RAPD primers. The dendrogram of Grevillea hybrids was performed using Neighbor-Joining analysis based on genetic distance. The analysis revealed that ‘Moonlight’, ‘Caloundra Gem’, and Little Pink Willie’ were clustered with Grevillea banksii. The three hybrids were hybrid of G. banksii and other Grevillea species. ‘Superb’ was closely related to ‘Robyn Gordon’ as they are hybrid of G. banksii and G. bipinnatifida.